Encryption of 3D or Higher-Dimensional Images: A Review - Renatta Nigro; Gabriel Ferreira; Maria Alice Andrade Calazans; Geovane Miguel; Felipe Alberto B. S. Ferreira; Verusca Severo; Francisco Madeiro (Applied Sciences)
This article aims to review encryption techniques for 3D or higher-dimensional images. Precisely, the following classes of images are considered: light field images, point clouds, and 3D medical images. The security and performance aspects of the encryption schemes for images are analyzed. It is observed that the number of papers with encryption in the transform domain exceeds the number of papers with encryption in the spatial domain. Additionally, it is observed that the application of encryption does not predominate in all the dimensions of the images, that is, the encryption does not occur completely in the image but rather through slices or sections. This review article summarizes several issues related to encryption techniques, technical perspectives for the future, and gaps in the literature.